2015
DOI: 10.1126/science.aaa8764
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid modulates colonization of the root microbiome by specific bacterial taxa

Abstract: Immune systems distinguish "self" from "nonself" to maintain homeostasis and must differentially gate access to allow colonization by potentially beneficial, nonpathogenic microbes. Plant roots grow within extremely diverse soil microbial communities but assemble a taxonomically limited root-associated microbiome. We grew isogenic Arabidopsis thaliana mutants with altered immune systems in a wild soil and also in recolonization experiments with a synthetic bacterial community. We established that biosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
780
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 971 publications
(888 citation statements)
references
References 56 publications
(42 reference statements)
40
780
2
8
Order By: Relevance
“…It is one of striking strategies to recruit a wide range of beneficial bacteria around plant rhizopshere (Lebeis et al 2015). The ability of plants to resist abiotic and biotic stresses can be enhanced by the intricately mutualistic interactions (Mishra et al 2014;Sukweenadhi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of striking strategies to recruit a wide range of beneficial bacteria around plant rhizopshere (Lebeis et al 2015). The ability of plants to resist abiotic and biotic stresses can be enhanced by the intricately mutualistic interactions (Mishra et al 2014;Sukweenadhi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the hairless caprice/triptychon (cpc/trt) and the excessive root hair werewolf/myb23 (wer/myb23) mutants had peak attraction of bacteria occurring about 1 h earlier than wild-type plants. There are obviously a large range of Arabidopsis mutants that could be tested in this way, including those involved in immune signaling (18) and root secretion such as ABC exporters (19). The alternative approach will be to use bacteria labeled with inducible fluorescent, luminescent (e.g., lux) (20)(21)(22), or FRET biosensors (23) to monitor root secretion and the bacterial response to roots.…”
mentioning
confidence: 99%
“…Arabidopsis engineered to produce cruciferous phytoalexins would enable the characterization of their physiological and ecological functions, for example, in interactions with beneficial and pathogenic microbes (42,43); our preliminary work in tobacco suggests that metabolic engineering of the indole phytoalexin pathway could also be extended to other crop plants. Furthermore, an analysis of the subcellular localization of pathway enzymes may shed light on the importance of trafficking of defense chemicals and the possibility of metabolon formation (44) to channel reactive intermediates.…”
Section: Discussionmentioning
confidence: 99%